A study to investigate the prevalence of metabolic syndrome in Chronic Obstructive Pulmonary Disease patients from North India - Kumar, Anand; Gupta, Sachin; Chaudhri, Sudhir; Verma, Sanjay Kumar; Kumar, Avdhesh; Sinha, S. K.; Gupta, Vishal; Kant, Surya (International Journal of Research in Medical Sciences, 2019)
Background: Worldwide, Chronic obstructive pulmonary disease (COPD) is the one of the leading cause of chronic morbidity and mortality. COPD is one of the diseases in which smoking is the common and important risk factor when it is associated with Metabolic syndrome (MetS). The individual components of MetS, i.e., obesity, dyslipidemia, fasting hyperglycaemia, and hypertension were independently associated with impairment of lung function too. The objective of this study is to find out the prevalence of metabolic syndrome among COPD patients. Methods: This was a cross-sectional study conducted in department of Respiratory Diseases and a total of 70 COPD patients were included in the study, which were enrolled for treatment from July 2016 to July 2017. The severity level in patients with COPD were determined according to GOLD (Global Initiative for Chronic Obstructive Lung Disease), 2015 guideline. International Diabetes Federation (IDF) guideline; (2005) was used in diagnosis of metabolic syndrome. Results: Seventy patients with COPD were enrolled during the study period. There were 45 males (64.2%) and 25(35.7%) females. Mean age of male patients was 58.67±9.87 years, while mean age of female patients was 57.23±10.4 years (35-87 years). Mean BMI of male was 24.33±6.64 kg/m2, while in case of female it was 30.07±6.95 kg/m2 and overall mean BMI of study population was 26.22±7.22 kg/m2. The mean waist circumference of male was 86.91±13.31 cm while in female it was 87.18±14.51 cm. The Overall prevalence of metabolic syndrome was 31.34% and most common in GOLD stage-3 (47.06%), followed by stage-2 (40%), followed by stage-4 (25.71%) and 7.4 % in GOLD stage -1. Conclusions: The presence of metabolic syndrome is common in patients with COPD and, all COPD patients should be considered for screening for it.